On Optimality of Tests of M-ary H ypotheses for Fixed Number of Independent - Haroutunian, Evgueni A. (Mathematical Problems of Computer Science, 2021)
The paper is devoted to the design of optimal approaches of testing of multiple simple hypotheses with samples of a fixed number of independent observations.